Anxiety Status and Influencing Factors of Rural Residents in Hunan During the Coronavirus Disease 2019 Epidemic: A Web-Based Cross-Sectional Survey - Zhang, Yi; Chen, Yi-ping; Wang, Jianjian; Deng, Yanhong; Peng, Dezhen; Zhao, Liping (Frontiers in Psychiatry, 2020)
Abstract Objective: To explore the status quo of anxiety and its influencing factors among rural residents in Hunan Province during the epidemic period of novel coronavirus pneumonia, and to provide an effective basis for the prevention and intervention of anxiety symptoms among rural residents. Methods: Convenience sampling was used. An electronic questionnaire was distributed to Hunan rural residents through the questionnaire star platform from February 26 to February 29, 2020. The general data and anxiety of Hunan rural residents were investigated, and the data were analyzed using SPSS 18.0. Results: The score of self-rating anxiety scale of 179 rural residents in Hunan was (40.93 ± 9.36) points. There were 32 cases had anxiety, including 26 cases of mild anxiety, 5 cases of moderate anxiety, and 1 case of severe anxiety. The detection rate of anxiety was 17.88%. There were statistically significant differences in the scores of self-rating anxiety scale for rural residents in Hunan with different health status, different degree of concerns about the epidemic, and different degree of impacts of the epidemic on their lives (P<0.05). The results of multiple linear regression analysis showed that self-perceived health status and the impact of the epidemic on life were the influencing factors of self-rating anxiety scale scores in rural residents of Hunan (P < 0.05). Conclusion: During the epidemic period of new coronavirus pneumonia, the detection rate of anxiety in rural residents in Hunan was higher than that of normal people in China. The relevant departments should pay attention to the mental health of rural general residents and take targeted mental health prevention and intervention measures under the epidemic situation.